Sociodemographic and health determinants of lifestyle changes during the COVID-19 pandemic in Oman - Basma Al Yazeedi; Azza Al Marshoudi; Hajar Alufi; Mallak Al Salmi; Dakariyat Al-Sharji; Yaqoob Al Hinai (Heliyon)
The COVID-19 pandemic preventive measures have successfully limited the spread of the infection but instituted changes in daily activities. This study examined the sociodemographic and health factors associated with lifestyle behavior changes among Omani adults during the COVID-19 pandemic. Sociodemographic factors investigated were age, gender, education, study (college versus non-college students), and marital status. A cross-sectional design was followed. We translated and tested a 20-item lifestyle behavior change during the COVID-19 pandemic questionnaire. A total of 515 responses were received with an average age of 25.7 years (SD ± 6.83). The participants' lifestyle behavior changes score mean was -2.75 (SD ± 9.08), indicating negative lifestyle change behavior. We found that lower lifestyle behavior changes scores were associated with younger age (p < .001), being single (p = .012), being a college student (p = .004), and having gained weight or were unsure about the weight change during the pandemic (p < .001). The linear regression model predicted a .19 increase in the lifestyle behavior change scores with each unit increase in age (B = .19, P = .02). Moreover, the model predicted more than a five-point decrease in the lifestyle behavior change scores among participants reporting a gain in weight or were unsure about the weight gain (B = −5.56, p < .001). These findings have significant implications for healthcare providers and policymakers. Actions to promote healthy lifestyle behaviors are essential to battle the increased risks of obesity after the pandemic, particularly among young adults. Additionally, mental and psychological wellbeing support during crises are vital for maintaining healthy lifestyle choices.